Global prevalence and risk factors for mental health problems in police personnel: a systematic review and meta-analysis - Syed, Shabeer; Ashwick, Rachel; Schlosser, Marco; Jones, Rebecca; Rowe, Sarah; Billings, Jo (Occupational and environmental medicine (London, England), 2020)
Police face an increased risk of developing mental health problems, yet reliable estimates of their psychological difficulties remain unknown. This systematic review and meta-analysis estimate the pooled prevalence and risk factors for mental health problems among police personnel worldwide. Three independent reviewers searched 16 databases and screened 11 506 articles published between January 1980 and October 2019. Eligible studies involved at least 100 active police professionals and used validated instruments to ascertain specific mental health problems. Estimates were pooled using random-effects meta-analyses. In total, 60 cross-sectional and seven longitudinal studies, involving 272 463 police personnel from 24 countries met criteria for inclusion. The overall pooled point prevalence was 14.6% for depression (95% CI 10.9% to 18.6%), 14.2% for post-traumatic stress disorder (PTSD; 95% CI 10.3% to 18.7%), 9.6% for a generalised anxiety disorder (95% CI 6.7% to 12.9%), 8.5% for suicidal ideation (95% CI 6.1% to 11.2%), 5.0% for alcohol dependence (95% CI 3.5% to 6.7%) and 25.7% for hazardous drinking (95% CI 19.6% to 32.4%). The strongest risk factor for depression and suicidal ideation was higher occupational stress, and the strongest risk factors for PTSD were higher occupational stress and avoidant coping strategies. Higher levels of peer-support were associated with significantly lower PTSD symptoms. Our findings suggest that the prevalence of mental health problems among police exceeds twice that previously reported in mixed samples of first responders, and is associated with poor social support, occupational stress and maladaptive coping strategies. Without effective intervention, psychological difficulties will remain a substantial health concern among police.